2014
DOI: 10.1186/1479-5876-12-105
|View full text |Cite
|
Sign up to set email alerts
|

ShaoYao decoction ameliorates colitis-associated colorectal cancer by downregulating proinflammatory cytokines and promoting epithelial-mesenchymal transition

Abstract: AbstractsBackgroundShaoyao decoction (SYD) is a traditional Chinese medicine prescription formulated by Liu Wan-Su, a master of traditional Chinese medicine in Jin-Yuan Dynasty. SYD is effective in treating ulcerative colitis. Paeonol, a component of SYD, inhibits colorectal cancer (CRC) cell proliferation and induces CRC cell apoptosis. In this study, azoxymethane (AOM)/dextran sodium sulfate (DSS)–induced colitis-associated CRC (caCRC) model and CRC cell lines were used to examine the effects of SYD on CRC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Thereby, tumor cells can penetrate the microvascular basic membrane more easily and be transported through the circulation to distant sites (6,30,31). Previous investigations have proven that some constituents of Chinese medicine function as suppressors of EMT (32)(33)(34). Our research team also confirmed that SYY inhibited the occurrence of EMT in HCC (20).…”
Section: Discussionsupporting
confidence: 71%
“…Thereby, tumor cells can penetrate the microvascular basic membrane more easily and be transported through the circulation to distant sites (6,30,31). Previous investigations have proven that some constituents of Chinese medicine function as suppressors of EMT (32)(33)(34). Our research team also confirmed that SYY inhibited the occurrence of EMT in HCC (20).…”
Section: Discussionsupporting
confidence: 71%
“…Shaoyao decoction is a Chinese medicinal formula consisted of 9 herbs. Study shows that the dose of 7.12 g/ kg increases the survival rate of DSS-induced UC mice and attenuates the expression levels of serum IL-1β, IL-6, TNF-α and NF-κB activation [135].…”
Section: Heat-clearing and Drying Dampness Categorymentioning
confidence: 94%
“…Suppress NF-κB activation [135] Qingchang Huashi recipe HT-29 cells Reduce the activation of NF-κB [137] Gegenqinlian Decoction TNBS-induced colon tissue Inhibit the activation and translocation of NF-κBp65 [138] DSS-induced colonic tissues Decrease the P-NF-κBp65 [139] RAW 264.7 cells Down-regulate the expression of P-NF-κBp65 [139] Jianpi Qingchang decoction DSS-induced colon tissue Inhibit the activation of the NF-κB [140] Modified pulsatilla decoction OXZ-induced colon tissues Suppress the activation of the NF-κB [142] Qing Hua Chang Yin DSS-induced colon tissue Inhibit the expression of the nuclear translocation of NF-κB [143] QingBai decoction DSS-induced colon tissue Decrease the protein level of P-NF-κBp65 [145] Chang-An-Shuan TNBS-induced colonic tissues Down-regulate the expression levels of NF-κBp65 [146] Baishaoqiwu TNBS-induced colon tissues Inhibit expression of the NF-ĸBp65 genes [147] Xie-xin decoction TNBS-induced colon tissues Decrease expression of NF-ĸBp65 [148] Compound sophorae decoction…”
Section: Shaoyao Decoction Aom/dss-induced Colonic Tissuesmentioning
confidence: 99%
“…This cycle was repeated twice. YTE‐17 (25 mg/kg/day) and Aspirin (30 mg/kg) were given orally for 12 weeks during the DSS treatment separately as previously described 1 . Aspirin is taken as a positive control, because it showed effectively inhibiting effect on intestinal adenomatous polyposis and colon carcinogenesis 22,23 .…”
Section: Methodsmentioning
confidence: 99%